Chapter 11 Ethnic majority and minority youth in multicultural societies - Cigdem Bagci, Sabahat; Rutland, Adam (Taylor & Francis, 2019)
Youth in Superdiverse Societies brings together theoretical, methodological and international approaches to the study of globalization, diversity, and acculturation in adolescence. It examines vital issues including migration, integration, cultural identities, ethnic minorities, and the interplay of ethnic and cultural diversity with experiences of growing up as an adolescent. This important volume focuses on understanding the experiences and consequences of multicultural societies and offers valuable new insights in the field of intergroup relations and the complexity of growingly heterogeneous societies. The book comprises four sections. The first includes fresh theoretical perspectives for studying youth development in multicultural societies, exploring topics such as superdiversity, globalization, bicultural identity development, polyculturalism, the interplay of acculturation and development, as well as developmental-ecological approaches. The second section highlights innovative methods in studying multicultural societies. It contains innovative dynamic concepts (e.g., experience-based sampling), methods for studying the nested structure of acculturative contexts, and suggestions for cross-comparative research to differentiate universal and context-specific processes. The third section examines social relations and social networks in diverse societies and features developmentally crucial contexts (e.g., family, peers, schools) and contributions on interethnic interactions in real-life contexts. The final section presents applications in natural settings and includes contributions on participatory action research and teachers dealings' with ethnic diversity. Each chapter provides a thorough overview of current research trends and findings, followed by detailed recommendations for future research, suggesting how the approaches can be cited, applied and improved. Youth in Superdiverse Societies is valuable reading for students studying adolescent acculturation and development in psychology, sociology, education, anthropology, linguistics and political science. It will also be of interest to scholars and researchers in social and developmental psychology, and related disciplines, as well as professionals in the field of migration.
English
Keywords: bic Book Industry Communication; bic Book Industry Communication; immigration; acculturation; adolescent development; bicultural identity; cultural identity; diaspora immigrant; ethnic identity; diaspora immigrants; ethnic identity; ethnic majority youth; family systems; immigrant youth's well-being; immigrants' social networks; immigration policies; minority groups; multicultural societies; polyculturalism; refugees; remote acculturation; super-diversity